What can adaptation to climate-related hazards tell us about the politics of time making? Exploring durations and temporal disjunctures through the 2013 London heat wave. Issue 85 (October 2017) - Nobert, Sébastien; Pelling, Mark
Abstract: Temporalities seem to have made a comeback as an object of geographical enquiries. Drawing on a set of in-depth interviews conducted with elderly residents of London during the heat wave of 2013, this paper explores temporal awareness through the concept of duration and its wider relevance to the geography of risk and the social studies of disasters. It argues that the overwhelming attention given to the logics of speed and urgency that underpin adaptation to climate change has restricted the capacity for geographers interested in risk and disasters to recognise distinct temporal perspectives and logics of action situated outside the open futures promoted by the concept of adaptation. The paper concludes by emphasising that a better comprehension of what temporal durations entail could also help to find different ways to understand and experience the inherent movements and changes that are intrinsic to time and to life more generally.